The Relationship between the Implementation of Effective Communication in Excellent Service with the Quality of Health Services in Class III Inpatients at Abdoel Wahab Sjahranie Hospital - Sumarni Sumarni; Nur Asiza; Muhammad Henry Gunawan (Institut Teknologi Kesehatan Dan Sains Wiyata Husada Samarinda, 2022)
Public services are part of achieving the government's goal of realizing an independent and prosperous society. So through this research, we want to see the relationship between the implementation of effective communication in excellent service with the quality of health services in class III inpatients at Abdoel Wahab Sjahranie Hospital. This type of research is an analytical survey with a cross-sectional research design, which is research where data is collected within a certain period of time. The population of this study was patients who were in the Tulip room at Abdoel Wahab Sjahranie Hospital, which numbered 55 people. The implementation of effective communication in excellent service with the Quality of Class III Inpatient services at Abdoel Wahab Sjahranie Hospital has a relationship that if done effectively will improve the image of Abdoel Wahab Sjahranie Hospital. The implementation of effective communication in excellent service with the Quality of Class III Inpatient services at Abdoel Wahab Sjahranie Hospital has a relationship that if done effectively will improve the image of Abdoel Wahab Sjahranie Hospital. The recommendations offered are that the management of Abdoel Wahab Sjahranie Hospital can consistently maintain a good work culture that prioritizes organizational nailai through equalizing perceptions of every apple or other activity.